Case report: Evaluation of head trauma in a tawny owl (Strix aluco) with advanced imaging diagnostic, FVEP and BAER test - Vetere, Alessandro; Camera, Nicola Della; Cococcetta, Ciro; Paoletti, Carlo; Dondi, Maurizio; Biaggi, Fabio; Ianni, Francesco Di (Frontiers in Veterinary Science, 2024)
An adult pet tawny owl (Strix aluco) presented to a veterinary hospital at Parma University with a history of head trauma. After a critical care protocol including thermal, oxygen and fluid support aimed at stabilizing the patient, a neurological examination was performed. During neurological evaluation, marked lethargy and an inability to rise from a recumbent position was noted. Anisocoria was also present, with a mydriatic left pupil exhibiting no pupillary light response (PLR) even on direct illumination of both eyes. On ocular fundus examination, retinal haemorrhage and retinal detachment were observed. Based on these clinical findings, a complete work-up was performed, including haematological exams and total body X-ray studies followed by a computed tomography (CT) scan. Additional examinations, such as brainstem auditory evoked response (BAER) measurement and flash visual evoked potential (FVEP) recording, were performed. FVEP measurements performed on the left eye exhibited no peaks in either series of stimulations, indicating an altered functional integration within the visual pathway. A CT scan revealed a large hypoattenuating lesion within the right cerebral hemisphere, suspected to be intraparenchymal edema. The BAER test demonstrated an altered trace consistent with brainstem involvement and left hypoacusis due to cranial nerve VIII deficiency. Head trauma can result in significant neurological impairments in birds, impacting their behaviour, mobility, and cognitive abilities. FVEP recordings, BAER tests and CT scans may be useful diagnostic tools in clinical practice. Understanding the causes and neurologic presentation of avian traumas is essential for effective prevention, diagnosis and treatment of affected birds.